Evaluation of a multi-scale WRF-CAM5 simulation during the 2010 East Asian Summer Monsoon. (November 2017) - Campbell, Patrick; Zhang, Yang; Wang, Kai; Leung, Ruby; Fan, Jiwen; Zheng, Bo; Zhang, Qiang; He, Kebin
Abstract: The Weather Research and Forecasting model with Chemistry (WRF-Chem) with the physics package of the Community Atmosphere Model Version 5 (CAM5) has been applied at multiple scales over Eastern China (EC) and the Yangtze River Delta (YRD) to evaluate how increased horizontal resolution with physics designed for a coarser resolution climate model impacts aerosols and clouds, and the resulting precipitation characteristics and performance during the 2010 East Asian Summer Monsoon (EASM). Despite large underpredictions in surface aerosol concentrations and aerosol optical depth, there is good spatial agreement with surface observations of chemical predictions, and increasing spatial resolution tends to improve performance. Model bias and normalized root mean square values for precipitation predictions are relatively small, but there are significant differences when comparing modeled and observed probability density functions for precipitation in EC and YRD. Increasing model horizontal resolution tends to reduce model bias and error for precipitation predictions. The surface and column aerosol loading is maximized between about 32°N and 42°N in early to mid-May during the 2010 EASM, and then shifts north while decreasing in magnitude during July and August. Changing model resolution moderately changes the spatiotemporal relationships between aerosols, cloud properties, and precipitation during the EASM, thus demonstrating the importance of model grid resolution in simulating EASM circulation and rainfall patterns over EC and the YRD. Results from this work demonstrate the capability and limitations in the aerosol, cloud, and precipitation representation of WRF-CAM5 for regional-scale applications down to relatively fine horizontal resolutions. Further WRF-CAM5 model development and application in this area is needed. Highlights: WRF-CAM5 adequately predicts meteorology and chemistry down to 4 km resolution. Overall good model performance for rain, but issues with convective vs. grid-scale rain. Model performance for rain improves with increasing horizontal resolution to 4 km. Widespread underpredictions in surface and column aerosol concentrations. WRF-CAM5 is limited for regional-scale applications of aerosol-cloud interactions.